Corporate Finance and investment : decisions and strategies - Pike, Richard (Prentice Hall, 2003)
This popular text has been extensively revised and updated for this fourth edition. Whilst significant new material has been added, the book continues to balance the conceptual and technical aspects of Corporate Finance, without allowing theory to dominate practice. Extensive examples illustrate how the concepts of financing and investment decisions can be applied to practical management and business policy issues. Corporate Finance and Investment is highly suitable for undergraduates studying for Accounting, Finance and Business Studies degrees, as well as for those taking MBA and other postgraduate level courses in corporate finance.